Evaluation of microbial contamination along the milk value chain in two districts of Tanzania - Hyera, E. (Sokoine University of Agriculture, 2015)
Milk is important as a valuable diet, but due to its nutritional value and perishable product it serves as an ideal medium for development of various microorganisms under suitable conditions, hence it is a staple food in epidemiology linked to zoonotic pathogens. This study was carried out in two districts in Tanga region (Northern Tanzania) to estimate microbial load, isolate selected pathogens and establish their possible sources or entry along the milk value chain. A total of 114 respondents were interviewed and subsequently milk samples were aseptically collected for laboratory microbial analyses using the standard ISO procedures for Food microbial analyses — Horizontal methods. The results revealed poor practices and lack of formal training on milk hygiene among most of the actors. More than 90% of all handled milk samples had Total plate count (TPC) above the EAC maximum acceptable standard of 2.0x105 CFU/ml. The overall mean coliform plate count (CPC) was 2.2x105 ± 1.9x105 CFU/ml, which indicated poor animal husbandry and hygiene practices. Least Squares Means have shown a statistical significant difference (P < 0.05) between households and milk suppliers for TPC and between households and street vendors for CPC. In the samples, one contained CPS isolate counting to 5.1x105 CFU/ml likely to cause staphylococcal poisoning. Isolated bacteria were Escherichia coli, Staphylococcus aureus and Listeria spp. including Listeria monocytogenes. Other microorganisms included Klebsiella spp., Proteus spp., Staphylococcus spp., Enterococcus faecalis, Bacillus cereus and Pseudomonas spp. Among identified pathogens, L. monocytogenes was most (42.1%) predominant. The quality of milk was poor; unhygienic practices, poor animal husbandry practices, organization of milk supply chains and dysfunction of the regulatory authorities predispose the public to risk of contracting milk-borne infections. Training on animal husbandry practices and public education on general milk hygiene are recommended. Also, sector policies, organizational structures, support services and research into public health risks in milk must be focused.